2019
DOI: 10.1021/acs.jpclett.9b02232
|View full text |Cite
|
Sign up to set email alerts
|

Phillips-Inspired Machine Learning for Band Gap and Exciton Binding Energy Prediction

Abstract: In this work, inspired by Phillips's ionicity theory in solid-state physics, we directly sort out the critical factors of the band gap's feature correlations in the machine learning architected with the Lasso algorithm. Even based on a small 2D materials data set, we can fundamentally approach an accurate and rational model about the band gap and exciton binding energy with robust transferability to other databases. Our machine learning outputs can reveal the exact physics pictures behind the predicted quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 52 publications
0
39
0
Order By: Relevance
“…5c). Inspired by Phillips's ionicity theory of solid-state physics, Liang et al [108] demonstrated a least absolute shrinkage and selection operator to predict the band energy and band gap. This method shows high accuracy and can be further extended to other databases ( Fig.…”
Section: Modeling Electronic Structure-(potential Energy Band Energymentioning
confidence: 99%
“…5c). Inspired by Phillips's ionicity theory of solid-state physics, Liang et al [108] demonstrated a least absolute shrinkage and selection operator to predict the band energy and band gap. This method shows high accuracy and can be further extended to other databases ( Fig.…”
Section: Modeling Electronic Structure-(potential Energy Band Energymentioning
confidence: 99%
“…Another vital application of accelerated development is artificial intelligence. Checking the excited-state properties of each molecule experimentally is time and energy consuming, and thus the use of quantum mechanical computation (QM) or machine learning algorithm (ML) is necessary in enabling scholars to study the structure and properties of material molecules more efficiently [11][12][13][14][15][16][17] and to compile large databases. However, quantum mechanical computation and machine learning algorithms, especially neural networks, are able to come up with relatively good performance only if large databases are utilized in training and debugging models.…”
Section: Background and Summarymentioning
confidence: 99%
“…Rajan et al used different regressions methods to predict bandgaps of MXene crystals using a training set of 76 G 0 W 0 bandgaps and a representation encoding atomic and structural properties 17 . Liang et al used a representation based on atomic ionicity descriptors to predict GW bandgaps of a set of 2D semiconductors 18 . In all these previous studies, the ML model was trained to predict the size of the bandgap rather than the full k -resolved band structure.…”
Section: Introductionmentioning
confidence: 99%